The Social Gospel and the Trust-Busters - Roberts, Robert R. (Church history, 1956)
By 1878 the United States stood on the verge of a period of immense consolidation and concentration of business wealth. Already the process was underway by means of pools and marketing agreements, and the powerful “trusts” were in the immediate future. By the turn of the century the characteristic feature of American business was the giant corporation, built on holding companies and interlocking directorates. The existence of such great wealth and power in the hands of a relatively few men posed a question for the interpreters of Christian ethics, and the answers ranged all the way from an idealistic communism to the benefits of stewardship.